From Comprehension to Expression: Exploring the Correlation of Listening and Speaking Anxieties in English as a Foreign Language (EFL) College Students - Marlina, Leni; Safitri, Dian; Adnan, Aryuliva; Aufa, Fauzul; Shawfani, Amalya (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2024)
Listening and speaking are two main English skills, which can determine the eligibility of EFL college students in comprehending the messages uttered by the speakers and delivering them through speaking. However, to obtain the better result of understanding the speakers and talking about the ideas in front of many other students and lecturers are demanding and it makes the students tend to have anxiety, which is called listening and speaking anxiety. The sample of research was one basic class of the English Language Education Program Specifically International Class EFL 30 Indonesia college students, the 2019 batch at English Language and Literature Department in one of public universities in West Sumatra. The type of sampling used was cluster random sampling. The findings suggested no link existed between the apprehension associated with oral communication and aural comprehension. The Pearson Correlation coefficient of .055, along with a two-tailed significance value of .760, provided support for the findings. Future studies are encouraged to further investigate the relationship between listening and speaking anxieties to gain a more comprehensive understanding of this topic.